Checklist of the aquatic and semiaquatic bugs (Hemiptera: Heteroptera: Gerromorpha, Leptopodomorpha & Nepomorpha) of Peru - Peralta-Argomeda, Jorge Luis; Rodrigues, Juliana Mourão Dos Santos; Huamantinco-Araujo, Ana; Moreira, Felipe Ferraz Figueiredo (Zootaxa, 2024)
The Peruvian fauna of aquatic and semiaquatic bugs comprises 233 species, representing 70 genera, 15 tribes, 29 subfamilies, and 16 families. Many of these species (22%) are endemic to the country, while 49% occur in Peru and other South American countries, 21% are found throughout the Neotropics, and 8% are widely distributed in the Americas. These proportions are similar among the three infraorders treated here. There is a slight predominance of Gerromorpha (48%) over Nepomorpha (46%) in Peru, and both are much more speciose than Leptopodomorpha (6%). The same Gerromorpha predominance also occurs in Colombia and Ecuador, whereas Nepomorpha is richer than Gerromorpha in Brazil, Argentina, and Chile. Within Peru, 92% of the species of aquatic and semiaquatic bugs have been recorded from the Atlantic slope, 16% occur in the Pacific slope, and only 2% in the Titicaca slope.